Effect of rehabilitation training combined with hyperbaric oxygen therapy on the nerve cytokine secretion and oxidative stress in rehabilitation period of patients with cerebral infarction - Ling Kong (Journal of Hainan Medical University, 2017)
Objective: To discuss the influence of rehabilitation training combined with hyperbaric oxygen therapy on the nerve cytokine secretion and oxidative stress in rehabilitation period of patients with cerebral infarction. Methods: A total of 110 patients with cerebral infarction who received rehabilitation therapy in the hospital between January 2015 and May 2017 were divided into routine group (n=55) and hyperbaric oxygen group (n=55) according to random number table. Routine group received regular rehabilitation training, and hyperbaric oxygen group underwent rehabilitation training combined with hyperbaric oxygen therapy. The differences in the serum contents of nerve factors, neurotransmitters and oxidative stress indexes were compared between the two groups at immediately after admission (T0) and after 14 d of treatment (T1). Results: At T0, there was no statistically significant difference in the serum contents of nerve factors, neurotransmitters and oxidative stress indexes between the two groups. At T1, serum nerve factors MBP and NSE contents of hyperbaric oxygen group were lower than those of routine group while NGF content was higher than that of routine group; serum neurotransmitter Glu content was lower than that of routine group while GABA content was higher than that of routine group; serum oxidative stress indexes ROS and LHP contents were lower than those of routine group while CAT and SOD contents were higher than those of routine group. Conclusion: Rehabilitation training combined with hyperbaric oxygen therapy can effectively optimize the nerve function and inhibit the systemic oxidative stress response in rehabilitation period of patients with cerebral infarction.